Correlation Between Sports-Related Maxillofacial Injuries and Head Injuries: A Five-Year Retrospective Study. Issue 4 (17th June 2022) - Park, Han-Kyul; Shriya, Jaiswai M.; Jeon, Min-A.; Choi, Na-Rae; Chen, Chun-Ming; Park, Jin-Young; Hwang, Dae-Seok
Abstract : Purpose: As sports have become more diverse and demanding, the number of patients with a maxillofacial injury accompanied by a cranial injury or neurological symptoms has increased. This study examined the correlation between sports-related maxillofacial injuries and head injuries. Patients and Methods: Among the patients who visited the emergency department of Pusan National University Dental Hospital due to a maxillofacial injury from sporting activities between 2014 and 2018, those who additionally had head injuries were retrospectively examined. Sporting activities were classified according to the American Academy of Pediatrics classification, and severity of injuries was determined using the Facial Injury Severity Scale (FISS). Patients whose medical records showed neurological symptoms and who underwent brain computed tomography for concomitant head injury were selected. The association between each of these variables, including age and gender, was statistically analyzed. Results: A total of 95 patients were included in this study, most of whom were male teenagers, and cycling was the most common cause of injuries. The meanFISS score was 0.79. Brain computed tomography was conducted for 91 patients, and 28 patients reported neurological symptoms. Only 11 patients underwent advanced evaluation in the neurology or neurosurgery department. Most patients were diagnosed with contusion and concussion and were monitored without any treatment. Conclusions: Higher FISS values did not reflect the severity of maxillofacial and head injury. In this study, there were some patients with cranial fracture and cerebral hemorrhage with mild neurosurgical symptoms of facial trauma. Although the incidence of head trauma is not high, the necessity of wearing protective equipment cannot be overemphasized because severe trauma is permanent. Neurological signs and symptoms of patients with maxillofacial trauma should not be overlooked and require a thorough evaluation.